2014
DOI: 10.1088/0004-6256/147/4/73
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF CLASS I METHANOL (CH3OH) MASER CANDIDATES IN SUPERNOVA REMNANTS

Abstract: We have used the Karl G. Jansky Very Large Array (VLA) to search for 36 GHz and 44 GHz methanol (CH 3 OH) lines in a sample of 21 Galactic supernova remnants (SNRs). Mainly the regions of the SNRs with 1720 MHz OH masers were observed. Despite the limited spatial extent covered in our search, methanol masers were detected in both G1.4−0.1 and W 28. Additional masers were found in Sgr A East. More than 40 masers were found in G1.4−0.1 which we deduce are due to interactions between the SNR and at least two sepa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 52 publications
(68 reference statements)
7
61
0
Order By: Relevance
“…Galactic class II masers are closely associated with young stellar objects (YSOs), which are often accompanied by OH and H 2 O masers, and are usually observed in one or two compact sites within a star formation region (e.g., Ellingsen 2006;Breen et al 2010;Caswell et al 2010). Class II masers are exclusively observed toward high-mass star formation regions (Breen et al 2013), while class I masers have been observed associated toward low-and high-mass star formation regions as well as supernova remnants (e.g., Kalenskii et al 2010;Pihlström et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Galactic class II masers are closely associated with young stellar objects (YSOs), which are often accompanied by OH and H 2 O masers, and are usually observed in one or two compact sites within a star formation region (e.g., Ellingsen 2006;Breen et al 2010;Caswell et al 2010). Class II masers are exclusively observed toward high-mass star formation regions (Breen et al 2013), while class I masers have been observed associated toward low-and high-mass star formation regions as well as supernova remnants (e.g., Kalenskii et al 2010;Pihlström et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This means they are most likely formed in different regions in the shocked gas Pihlström et al 2014;McEwen et al 2014). The majority of the 44 GHz masers in the NE region have slightly lower velocity spread compared to the OH masers, which have an average of ∼ 57 km s −1 , and are located just to the SW of the group of 44 GHz CH 3 OH masers (in the rectangle region).…”
Section: Ne Regionmentioning
confidence: 98%
“…So-called 'class I' CH 3 OH masers are commonly associated with the molecular shocks of HII regions, but in the case of Region W, no such counterpart was identified, leaving the W28 shock as the most plausible trigger mechanism [25]. CH 3 OH masers might be a more-numerous, but less-intense, tracer of SNR shocks than 1720 MHz OH masers [39]. Furthermore, the existence of cospatial CH 3 Figure 2), and are associated with a dense molecular clump, hereafter referred to as the "Region Y clump", at a line of sight central velocity of ∼21 kms −1 , which is ∼8-12 kms −1 (see "Core 1" in [22]) faster than the central velocity of the gas component unambiguously shown to be associated with W28 and HESS J801−233.…”
Section: The Shocked Molecular Cloud Towards Hess J1801−233mentioning
confidence: 99%